Dual Stressors and Female Pre-school Teachers' Job Satisfaction During the COVID-19: The Mediation of Work-Family Conflict - Hong, Xiumin; Liu, Qianqian; Zhang, Mingzhu (Frontiers in Psychology, 2021)
Online education has become a vital weapon to fight against the COVID-19 epidemic in the world. In the home-based online education environment, female pre-school teachers are expected to balance the dual roles of teacher and mother at the same time, which may trigger the work-family conflict. Although previous studies analyzed individual stressors, work-family conflict and its outcomes, there is little research on pre-school teachers' work and parenting experience during major public health emergencies. The current study examined the associations among work overload, parenting stress, work-family conflict, and job satisfaction during the COVID-19. Seven hundred eighteen female pre-school teachers with children who worked online at home participated in the study. Female pre-school teachers reported that the COVID-19 has increased work overload and parenting stress. Moreover, work overload was negatively associated with job satisfaction via its positive association with work-to-family conflict. Parenting stress was negatively associated with job satisfaction via both family-to-work conflict and work-to-family conflict. The study contributes to a better understanding of the association among female pre-school teachers' work overload, parenting stress, work-family conflict, and job satisfaction. Our findings highlighted potential avenues for interventions aimed at balancing female pre-school teachers' work and family and improving their job satisfaction during the COVID-19.